Analysis of Generation-Z Female Students' Islamic School Reception Towards the Performance and Stage Action of the Heavy Metal Band Voice of Baceprot - Lisdayanti Oktiana; Muhamad Husni Mubarok; Nurhana Marantika (Sahafa Journal of Islamic Communication, 2024)
Voice of Baceprot (VoB) stands out as an oase in the midst of the dwindling presence of heavy metal bands in Indonesia. The band had a rapid increase in popularity when the public was presented with its members wearing hijabs. Within a little timeframe, this band swiftly gained global attention. This study aims to analyse the appearance and stage performance of the heavy metal band VoB, focusing on the perspectives of female students from Generation Z at two distinct types of Islamic boarding schools: traditional and modern. This study employed descriptive methodologies with qualitative approach. In order to enhance this research, the reception analysis technique developed by Stuart Hall was employed to ascertain the perspective of each informant in viewing VoB's performance, encompassing both verbal and non-verbal communication. The data collection encompasses interviews, observation, and literature review. Research indicates that female students at Traditional Islamic Boarding Schools differ from those at Modern Islamic Boarding Schools in terms of personal beliefs, values, and educational backgrounds. Traditional Islamic boarding schools have more open, whilst Modern Islamic boarding schools are more rigorous.   Keywords: Female Student of Islamic School, Appearance, Stage Performance, Voice of Baceprot